Análisis de los costos de producción de plantas de vivero en San Pedro (Buenos Aires, Argentina) - Hansen, Laura; Heguiabeheri, Adolfo Ricardo; Varela, Lucila (Universidad Nacional de Hurlingham, 2023)
Poster